Menaquinone (Vitamin K(2)) Biosynthesis: Localization and Characterization of the menA Gene from Escherichia coli - Suvarna, K. (American Society for Microbiology, 1998)
A key reaction in the biosynthesis of menaquinone involves the conversion of the soluble bicyclic naphthalenoid compound 1,4-dihydroxy-2-naphthoic acid (DHNA) to the membrane-bound demethylmenaquinone. The enzyme catalyzing this reaction, DHNA-octaprenyltransferase, attaches a 40-carbon side chain to DHNA. The menA gene encoding this enzyme has been cloned and localized to a 2.0-kb region of the Escherichia coli genome between cytR and glpK. DNA sequence analysis of the cloned insert revealed a 308-codon open reading frame (ORF), which by deletion analyses was shown to restore anaerobic growth of a menA mutant. Reverse-phase high-performance liquid chromatography analysis of quinones extracted from the orf-complemented cells independently confirmed the restoration of menaquinone biosynthesis, and similarly, analyses of isolated cell membranes for DHNA octaprenyltransferase activity confirmed the introduction of the menA product into the orf-complemented menA mutant. The validity of an ORF-associated putative promoter sequence was confirmed by primer extension analyses.